Women’s Empowerment in The Matriarch of Kamathipura, a part of Hussain Zaidi’s Mafia Queens of Mumbai - Irwan Sumarsono; Ima Masofa (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Women’s oppression and discrimination occur in many places in the world, especially in developing nations. To end this oppression and discrimination, it is important to empower women so that they know that they are oppressed and discriminated against. Women’s empowerment also makes women independent, skillful, educated, and able to compete against their opponents. This study focused to analyze the women’s empowerment reflected in The Matriarch of Kamathipura, an episode of S. Hussain Zaidi’s Mafia Queens of Mumbai, especially on how the main character, Gangubai Kathiawadi, fought to empower women in her area to get the equality as the men had. The researchers used the theory of feminism to analyze this study. The study’s main source was the book Mafia Queens of Mumbai, while the supporting data were derived from English literature journals, e-books, and other internet sources. This research used a qualitative method which was based on library research. The collected data were analyzed, discussed, and presented to the readers. The study found that Gangubai successfully empowered women from the lower class to have the same rights, services, and equality in society using the ability, capability, and networking she built. Gangubai empowered them by advocating their rights, fighting against discrimination, and demanding the performance and patterns that generate difference and segregation. This study was expected that it would make readers know that men and women are equal in that they have the same right and responsibilities, and they will disagree with the oppression and discrimination against women.